Interactive cultural narratives: unveiling the potential of the 3D serious game maker tool for Kristang culture - Abdulrazic, Mostafa Osama Mostafa (2025)
Culture is a cornerstone of identity, yet many cultures face the risk of fading into obscurity despite efforts to preserve them through various mediums. Leveraging the concept of 3D serious games and basing the research on key learning theories like the maker pedagogy and multiliteracies theory, this research aims to educate children about culture by developing a 3D game maker tool that implements key elements of the researched learning theories. The goal is to empower users aged 12 and older to effortlessly create serious 3D cultural games in a first-person view, enriching the experience with IoT and AI features. Additionally, the tool facilitates gameplay of games crafted using the same platform, fostering social interaction and aligning with effective forms of learning.